2008
DOI: 10.1021/bi800904m
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Mechanism of Protein Arginine Methyltransferase 1

Abstract: Protein arginine methyltransferases (PRMTs) are SAM-dependent enzymes that catalyze the mono- and di-methylation of peptidyl arginine residues. Although all PRMTs produce mono-methyl arginine (MMA), type 1 PRMTs go on to form asymmetrically dimethylated arginine (ADMA), while type 2 enzymes form symmetrically dimethylated arginine (SDMA). PRMT1 is the major type 1 PRMT in vivo, thus it is the primary producer of the competitive NOS inhibitor, ADMA. Hence, potent inhibitors, which are highly selective for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 37 publications
15
90
3
Order By: Relevance
“…1F), significantly exceeding the enzyme concentration of 10 nM, and production of di-methylated peptide could not be observed until the concentration of the monomethylated peptide exceeded that of the unmethylated substrate. This result demonstrates that PRMT5 has a nonprocessive enzymatic mechanism for peptide substrates, in contrast to the partially processive mechanism described for PRMT1 (36). Lack of processivity for the PRMT5 or PRMT5:MEP50 complex was observed at all tested concentrations of the peptide (0.01-10 μM) and AdoMet (0.1-10 μM).…”
Section: Resultsmentioning
confidence: 65%
“…1F), significantly exceeding the enzyme concentration of 10 nM, and production of di-methylated peptide could not be observed until the concentration of the monomethylated peptide exceeded that of the unmethylated substrate. This result demonstrates that PRMT5 has a nonprocessive enzymatic mechanism for peptide substrates, in contrast to the partially processive mechanism described for PRMT1 (36). Lack of processivity for the PRMT5 or PRMT5:MEP50 complex was observed at all tested concentrations of the peptide (0.01-10 μM) and AdoMet (0.1-10 μM).…”
Section: Resultsmentioning
confidence: 65%
“…Several experimental studies have been performed to address this question. [27][28][29][30] For Type I enzymes, it was proposed that the active site methionine residues might prevent the binding of -MMA in a conformation that allows the formation of symmetric product. For Type II enzymes, this position is occupied by the residues with smaller side chains, such as Ser as observed in PRMT5.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also suggested that -MMA formation was not obligatory. 27 -MMA might be further methylated to form ADMA before being released from the active site. These results along with the previous suggestion that both methyl groups were added to the N 2 atom explain why the asymmetric product is formed from the PRMT3-catalyzed reaction.…”
Section: First and Second Methylations On The N 2 Atommentioning
confidence: 99%
“…These peptides are used as substrates of PRMT1 and PRMT5 to evaluate how different acetylation combinations affect the methylation of Arg-3 catalyzed by these two enzymes. It is worthwhile to stress that our data and others have fully determined that the N-terminal H4 peptide sequence represents an authentic substrate of PRMT1, and its catalytic properties are very similar to that of the full-length H4 protein (50). All the peptides were synthesized using the standard Fmoc SPPS protocols, purified on C-18 reversed phase HPLC column, and confirmed with MALDI-MS as described previously (51).…”
Section: Design Synthesis and Characterization Of Modified H4mentioning
confidence: 93%